Implementation of a Weather Station Using FPGA with Real Time Data Access and Analysis - Santillán Carranza, Holger Jorge (2025)
The present study develops a weather station with the Fiel-Programmable Gate Array (FPGA) technology to obtain meteorological data in educational environments, but that can be adapted to any real scenario, using ADM1001 sensors for temperature and humidity, amount of rain, wind direction and wind speed. The proposed design aims to improve the accuracy and speed with which weather data is obtained in real time. For this purpose, the Elvis II+ platform together with the Xilinx Spartan 3E FPGA was used for the connections of the different types of sensors. In addition, the LabVIEW programming environment was used for the design and control of the system ensuring a user-friendly interface for the users. To present the collected data, a Node-Network solution was developed to efficiently visualize the data, the algorithms used achieved an accuracy of 85% under normal conditions, the root mean square error (RMSE) was 0.2 °C for temperature and 1.5% for humidity. This visualization is achieved through a Raspberry Pi since it facilitates the access and management of the meteorological information collected in real time, which endorses the quality of the prototype designed in the present work.